Crack tip shape effect on stress-strain fields in plastically compressible materials. (September 2019) - Alam, M I; Khan, D; Mittal, Y; Kumar, S
Abstract: In the present study, the effects of crack tip shape on near tip deformation and fields are numerically investigated for a mode I crack under plane strain and small scale yielding conditions. The material is characterized by finite strain elastic-viscoplastic constitutive relation with bi-linear hardening and hardening-softening-hardening hardness functions. Both plastically incompressible and compressible solids have been considered for analyses. It has been observed that the combination of crack tip profile and plastic compressibility has significant effect on the near tip deformation and plastic fields.